2005
DOI: 10.1002/jts.20019
|View full text |Cite
|
Sign up to set email alerts
|

Physiological arousal and dissociation in acute trauma victims during trauma narratives

Abstract: The aim of the present study was to examine whether the finding of suppressed physiological activity in dissociative rape-trauma victims (Griffin, Resick, & Mechanic, 1997) was replicable in a nonsexual assault trauma group. A sample of 17 high-dissociating (HD) participants and 18 low-dissociating (LD) participants who had experienced a motor vehicle accident or physical assault described their trauma while skin conductance, heart rate activity, and self-reported mood were recorded. HD individuals demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 20 publications
1
33
1
Order By: Relevance
“…Assessing the construct validity of these two RSDI subscales, however, is not straightforward. In fact, inconsistent findings were expected across samples, because (1) avoidance and dissociation may arise immediately or after substantial reexperiencing, (2) dissociative disorders (e.g., sample 2) may entail unique relationships between state dissociation and other variables, and (3) conflicting findings have been reported on relationships between dissociation and HR reactivity in different samples (Griffin et al 1997;Nixon et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Assessing the construct validity of these two RSDI subscales, however, is not straightforward. In fact, inconsistent findings were expected across samples, because (1) avoidance and dissociation may arise immediately or after substantial reexperiencing, (2) dissociative disorders (e.g., sample 2) may entail unique relationships between state dissociation and other variables, and (3) conflicting findings have been reported on relationships between dissociation and HR reactivity in different samples (Griffin et al 1997;Nixon et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Because avoidance could occur from the outset or after engagement with trauma-related stimuli had occurred and physiological reactivity had manifested, small correlations were tentatively predicted for correlations between RSDI Avoidance and HR reactivity. Based on prior conflicting findings with respect to dissociation and physiological reactivity (e.g., Griffin et al 1997;Nixon et al 2005), as well as the possibility that dissociation could occur immediately or later in the process, no general prediction was made with regard to correlations between RSDI Dissociation and HR reactivity across both samples. However, though sample 2 did not differ from the other two clinical samples on the measure of trait dissociation (see below), it was thought that qualitative differences associated with suffering from a dissociative disorder could manifest as different relationships between RSDI Dissociation scores and HR reactivity in response to the trauma script.…”
Section: Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Nixon, Bryant, Moulds, Felmingham, and Mastrodomenico (2005) found in their sample of motor vehicle accident or physical assault victims that heightened levels of peritraumatic dissociation tended to be accompanied by raised autonomic responsivity (i.e., elevated heart rate; see also Ladwig et al, 2002). However, these studies have investigated the relationship between peritraumatic dissociation during trauma and physiological responsivity at a later point in time (i.e., weeks, months, or years after the trauma).…”
mentioning
confidence: 90%
“…Several studies have not found differences in autonomic arousal between dissociative and nondissociative individuals with PTSD [123][124][125]. It appears that our current understanding of the role of dissociation in relation to arousal is very limited, and it is unclear whether there is sufficient evidence to include a unique dissociative subtype of PTSD in DSM-5.…”
Section: Subtypes Of Ptsdmentioning
confidence: 97%